Sintesis Katalis Berbasis Platina Didukung Reduced Graphene Oxide Dan Karakterisasinya Menggunakan Pengujian Cyclic Voltammetry - Darmayasa, Komang Gede; Joni, I Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract In an era that increasingly prioritizes environmentally friendly technology, the development of Proton Exchange Membrane Fuel Cells (PEMFC) has become a key focus in the field of energy conversion. This study aims to synthesize platinum (Pt)-based catalysts supported by reduced Graphene Oxide (rGO) through a modified Hummer's method and to evaluate the effect of varying the mass ratio of H?PtCl? to Graphene Oxide (GO) on the characteristics of the resulting catalysts. The synthesis was carried out using a modified Hummer's procedure to produce rGO, which was then combined with Pt through a chemical reduction process. The synthesized catalysts were tested using Scanning Electron Microscopy (SEM) to observe surface morphology and Cyclic Voltammetry (CV) to assess the electrochemical activity of the produced catalysts. The results show that varying the mass ratio of H?PtCl? to GO affects the morphology and electrochemical activity of the Pt/rGO catalysts. Catalysts with certain compositions exhibited more uniform Pt particle distribution and smaller particle sizes, contributing to enhanced electrochemical activity. This study contributes to developing more efficient catalysts for PEMFC applications, particularly in improving current density and operational stability. Keywords: PEMFC, Pt/rGO Catalyst, Reduced Graphene Oxide, Hummer Method, Catalyst Synthesis